Snowblind: a brief career in the cocaine trade - Sabbag, Robert (The Bobbs-Merrill Company)
"In this "witty, intelligent, fiercely stylish, drug-induced exemplary tale" (Los Angeles Times), Sabbag masterfully traces Zachary Swan's Roman-candle career, from his first forays into smuggling marijuana to his jaunts to Colombia to buy pure cocaine, and his ever more elaborate plans to outwit the police and customs officials"--Amazon.com